Reduksi Energi Pengolahan Air Limbah di Kawasan Industri Dengan Implementasi Teknologi Food Chain Reactor (Studi Kasus : Kawasan Industri Jababeka Bekasi) - Temmy Wikaningrum; Rijal Hakiki (Jurnal Serambi Engineering, 2020)
Biological-aerobic process is a technology that is often chosen to treat wastewater in industrial areas, especially industries related to food industries. Compared to chemical treatment and advanced treatment, biological treatment is relatively more efficient in the costs required. However, in conventional biological treatment the amount of energy consumption in the process is a major cost component that it becomes one of the challenges in implementing this technology. This paper contains a review of the implementation of the Food Chain Reactor (FCR) technology in treating industrial area wastewater, focusing on an overview of energy consumption compared to conventional biological-aerobic treatment of oxidation ditch (OD). FCR is a wastewater treatment plant (IPAL) that combines Integrated Fixed Film Activated Sludge (IFAS) technology and technology that resembles Constructed Wetland, thus enabling the simultaneous physical, biological and biochemical treatment processes within the reactor. In this case study, the implementation succeeded in showing a reduction in energy consumption by 46.4% while maintaining an efficiency decrease in BOD by 83% and efficiency in decreasing ammonia by 82%. As with the OD process, in this FCR study showed that the denitrification process has not been successful.